O modelo de organização social de cultura em São Paulo: potencialidades e fragilidades após sua implantação - Matta, Beatriz (2013)
This study examines the strengths and weaknesses of the Organização Social model in the cultural sector from the experience of its implementation by the government of the state of São Paulo. The analysis is carried out with parameters - autonomy, management and interrelationship between policy formulation and implementation derived from the literature on the subject and applied to three selected cases. As a management model that involves the relationship between government and non-governmental organization, the degree of interference of these parameters in the State Department of Culture and in selected cases is analyzed with the aim of identifying how they affect the performance of Organização Social and the implementation of public culture policies. Even though previously defined parameters and features throughout this study affect policy implementation and the deployment of the model in different ways, it can be concluded that the model moves towards consolidation, although it still requires special attention from both parties, especially the government.